2020
DOI: 10.3389/fmars.2020.00207
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Lithogenic Inputs to the Southern Ocean Using Long-Lived Thorium Isotopes

Abstract: Thorium (Th) isotopes were applied to quantify the supply of lithogenic inputs from the Kerguelen Plateau to the Southern Ocean. The dissolved concentrations of 232 Th and 230 Th were measured following a novel pre-concentration method using the Nobias resin from 10 stations above and on the slopes of the plateau. Elevated 232 Th/ 230 Th ratios in the upper 500 m of the water column confirm the input of lithogenic material from islands, glaciers and the resuspension of shelf-deposited sediments. 230 Th concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 83 publications
1
10
0
Order By: Relevance
“…1950) levels (Δ 14 C atm , ShCal13, error bars show 1σ-standard deviations (SD)) 26 compared to predicted (i.e. modelled) 14 C changes in the atmosphere due to variations in cosmogenic production 3 (with error bars showing 1σ-SD), b production-corrected 3 variations in Δ 14 C atm , with error bars showing 1σ-SD, c atmospheric CO 2 (CO 2,atm ) variations 32 , and d Antarctic temperature variations represented by water isotope changes, δD, in the Antarctic EPICA Dome C (EDC) ice core 25 , and e water isotope changes, δ 18 O, in Greenland ice core NGRIP 74 . Vertical bars indicate intervals of rising CO 2,atm levels.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1950) levels (Δ 14 C atm , ShCal13, error bars show 1σ-standard deviations (SD)) 26 compared to predicted (i.e. modelled) 14 C changes in the atmosphere due to variations in cosmogenic production 3 (with error bars showing 1σ-SD), b production-corrected 3 variations in Δ 14 C atm , with error bars showing 1σ-SD, c atmospheric CO 2 (CO 2,atm ) variations 32 , and d Antarctic temperature variations represented by water isotope changes, δD, in the Antarctic EPICA Dome C (EDC) ice core 25 , and e water isotope changes, δ 18 O, in Greenland ice core NGRIP 74 . Vertical bars indicate intervals of rising CO 2,atm levels.…”
mentioning
confidence: 99%
“…In addition, sedimentation in these areas can be highly dynamic with common occurrences of highaccumulation drift deposits 14,15 , often preventing robust age models to be developed. In particular, stratigraphic alignments of sedimentary iron concentrations to Antarctic ice-core dust as recently employed for the Southwest Indian Ocean 16 may be problematic as the lithogenic fraction may likely not be solely of aeolian origin 17,18 . Many of these limitations were circumvented through paired uranium series-and 14 C-dated corals in the Drake Passage upwelling hotspot region 8 complemented by deep-ocean 14 C ventilation reconstructions from the South Atlantic 5 .…”
mentioning
confidence: 99%
“…Therefore, the lack of relationship of Fe distributions and N * (Figure S4), the modest increase of dFe and dMn (up to ∼7 and 11 nmol kg −1 , respectively; Figures 3a and S4), the overwhelming dominance of lithogenic pFe (Figures 3 and S2) and the strong sediment resuspension events (Figure 5), all point to non‐reductive sedimentary sources (desorption/dissolution) of Fe in the CAA. Non‐reductive dissolution of lithogenic material is increasingly being recognized as an important, but often underestimated, source of Fe to ocean waters in the Pacific, Atlantic and Southern oceans (Abadie et al., 2017; Conway & John, 2014; Homoky et al., 2016; Pérez‐Tribouillier et al., 2020). Although no trace metal samples were collected in Jones Sound and Nares Strait during the Canadian GEOTRACES GN02 and GN03 cruises, similar processes are expected to control Fe distributions in these regions, where transmissivity drops and tidal stresses (and thus the prevalence of sediment resuspension) are comparable to those in the central sills area of the CAA (Figures 5 and S3).…”
Section: Resultsmentioning
confidence: 99%
“…Reductive dissolution of Fe in oxygen‐deficient continental sediments has long been documented as the dominant input mechanism of dissolved species of Fe at the sediment‐water interface (Burdige, 1993; Elrod et al., 2004; Severmann et al., 2010). However, more recently, non‐reductive sedimentary dissolution has been proposed as a major source of dissolved Fe (Abadie et al., 2017; Conway & John, 2014; Homoky et al., 2016; Jeandel & Oelkers, 2015; Pérez‐Tribouillier et al., 2020; Radic et al., 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Observational data suggest that Fe is sourced from continental shelf sediments and supplied via lithogenic particles (Pérez‐Tribouillier et al., 2020). Model studies have demonstrated that lithogenic particles can also have a significant impact on both the source and sink of DFe (Beghoura et al., 2019; Pagnone et al., 2019; Ye & Völker, 2017).…”
Section: Discussionmentioning
confidence: 99%